PENINGKATAN KECERDASAN KINESTETIK ANAK MELALUI TARI KE SAWAH DI TAMAN KANAK-KANAK TOYIBAH TALAWI - Yusvarita, Yusvarita (Universitas Negeri Padang, 2012)
Underdeveloped children’s kinesthetic intelligence in kindergarten Toyibah Talawi, therefore researcher conducted a study using Tari Ke Sawah as a learning strategy. The purpose of this research is to improve the children’s kinesthetic intelligence. Researcher uses the Mixing Method which is a mixture of methods, the quantitative and qualitative approaches. Action research was conducted with 2 cycles. The results obtained in the second cycle, an increase in child kinesthetic intelligence. Based on these result, it can be concluded that the Tari Ke Sawah can improve the children’s kinesthetic intelligence in kindergarten Toyibah Talawi Sawahlunto.